A transferable telepsychiatry model for improving access to emergency mental health care. (October 2014) - Saurman, Emily; Johnston, Jarret; Hindman, James; Kirby, Sue; Lyle, David
The Mental Health Emergency Care-Rural Access Programme (MHEC) aims to improve access to specialist emergency mental health care in rural and remote communities in New South Wales. It provides a range of services including emergency telephone triage and video assessment. The present report provides a detailed description of the structure and function of the MHEC model, and identifies matters concerning adaptation and transferability. Structure: the MHEC can be contacted 24 hours/day, every day of the year; no caller is refused assistance. Function: the MHEC provides information services, clinical services and other programme activities. Adaptation of the model and implementation elsewhere (transferability) should be informed by local needs, existing practices and the components of access. The programme has already attracted the attention of two other regions in Australia interested in implementing emergency telepsychiatry programmes. The MHEC model is a practical solution for improving access to specialist emergency mental health care in underserved areas.